(untitled) (Diyala Journal of Engineering Sciences, 2024)
The detrimental impact of corrosion on industrial metals, especially mild steel under acidic conditions, underscores the need for the development of effective corrosion inhibitors. In the present work, a new anticorrosion chemical named 2-(2-anthracen-9-yl)-3-chloro-4-oxoazetidin-1-y1)-1- methyl-1H-imidazol-4(5H)-one (AOMI) was synthesized, identified, and assessed for the protection of low-carbon steel corrosion in one molar hydrochloric acid solution. Experimental procedures included weight loss, electrochemical, surface morphological, FTIR, 1H NMR, and hardness measurements, while computational analyses involved quantum chemical calculations. The investigation revealed that AOMI significantly reduced corrosion rates with maximum inhibition efficiencies of 90% at 80 ppm and 60 oC. A spontaneous monolayer was formed on the metal surface. The adsorption of this layer was according to the Langmuir isotherm. SEM and AFM images showed the presence of the protective layer. The experimental results were validated by computational simulations, which showed that bonds were formed with the mild steel surface.